A Descriptive Study To Assess The Knowledge Level Regarding Mental Illness Among Young Adults In Badshahpur Village, Gurugram - Chauhan, Tarun; Bansal, Siddharth Kumar; Tokas, Manurut (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research was to identify the knowledge towards mental illness among adults. The study was descriptive in nature. A total of 50 adults participated. A quantitative approach was used for the present study. A convenient sampling technique was used to select the samples. The data collection tools used were demographic profile, semi structured knowledge questionnaire. The pilot study was done on 6 adults who met the sampling criteria. In this study analysis shows that majority of the subjects 30(66.7%) had moderately adequate knowledge, 16(26.7%) had inadequate knowledge and 4(6.7%) had adequate knowledge. In conclusion, this study marks that poor knowledge about the cause and nature of mental illness is common in the community. Even though there are many steps taken by the Indian Government to treat and rehabilitate the mentally ill, stigma continue to persist and it’s still a barrier for people with mental illness.